2003
DOI: 10.1007/s00280-003-0620-1
|View full text |Cite
|
Sign up to set email alerts
|

Saline, mannitol, and furosemide hydration in acute cisplatin nephrotoxicity: a randomized trial

Abstract: Hydration with saline or saline + furosemide appears to be associated with less cisplatin nephrotoxicity than saline + mannitol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
139
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 19 publications
3
139
1
5
Order By: Relevance
“…(14) A third randomized trial of cisplatin at a dose of 75 mg/m 2 and hydration alone, hydration with mannitol, or hydration with furosemide showed that creatinine clearance did not change before or after cisplatin treatment in the hydration alone and the furosemide-treated groups, but decreased in the mannitol-treated group. (15) However, these randomized trials included only small numbers of patients and therefore are not conclusive. Thus, no reports have convincingly shown any advantage of diuretics in preventing cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…(14) A third randomized trial of cisplatin at a dose of 75 mg/m 2 and hydration alone, hydration with mannitol, or hydration with furosemide showed that creatinine clearance did not change before or after cisplatin treatment in the hydration alone and the furosemide-treated groups, but decreased in the mannitol-treated group. (15) However, these randomized trials included only small numbers of patients and therefore are not conclusive. Thus, no reports have convincingly shown any advantage of diuretics in preventing cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Indeed, irreversible renal damage occurs in about one-third of cisplatin-treated patients despite using known prophylactic methods like hydration. [4,5] There is almost a century of literature that supports the concept that prior injury may protect the kidney against a second insult, and it has been shown more recently that the primary stimulus may not necessarily reach the injurious level. [6] For example, sub-lethal short ischemic periods may attenuate subsequent renal functional or structural damage induced by prolonged ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…27 Despite various hydration protocols designed to minimize the nephrotoxicity, approximately one-third of patients who receive cisplatin develop evidence of acute renal failure. 28 Cisplatin accumulates in all nephron cells, but especially in the proximal kidney tubule cells within the S3 segment, which bear the brunt of the damage. 27 We did not observe any case of nephrotoxicity in the patients in the current study, although they had been previously treated with platinum compounds.…”
Section: Discussionmentioning
confidence: 99%